45th AIAA Fluid Dynamics Conference 2015
DOI: 10.2514/6.2015-2625
|View full text |Cite
|
Sign up to set email alerts
|

Computations of Disturbance Amplification Behind Isolated Roughness Elements and Comparison with Measurements

Abstract: Computations are performed to study laminar-turbulent transition due to isolated roughness elements in boundary layers at Mach 3.5 and 5.95, with an emphasis on flow configurations for which experimental measurements from low disturbance wind tunnels are available. The Mach 3.5 case corresponds to a roughness element with right-triangle planform with hypotenuse that is inclined at 45 degrees with respect to the oncoming stream, presenting an obstacle with spanwise asymmetry. The Mach 5.95 case corresponds to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…The streamwise evolution of these roughness-induced streaks has been studied by various authors [15][16][17][18][19][20]. For supersonic and hypersonic boundary layers, it has been observed that long-lived streamwise streaks can support instability modes that did not exist in the absence of the roughness element [21][22][23]. In general, roughness elements having a symmetric (asymmetric) shape have been found to support a dominant convective instability mode symmetrically (asymmetrically) distributed around the wake centerline [21].…”
Section: Introductionmentioning
confidence: 99%
“…The streamwise evolution of these roughness-induced streaks has been studied by various authors [15][16][17][18][19][20]. For supersonic and hypersonic boundary layers, it has been observed that long-lived streamwise streaks can support instability modes that did not exist in the absence of the roughness element [21][22][23]. In general, roughness elements having a symmetric (asymmetric) shape have been found to support a dominant convective instability mode symmetrically (asymmetrically) distributed around the wake centerline [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, most investigations have been performed on flat plates with a zero pressure gradient (ZPG) and a detailed study on the influence of different pressure gradients on roughness wake-flow instabilities is still missing. Theiss and Hein 27 and Theiss et al 28 used LST-2D to characterize the most amplified wake modes behind different roughness elements in the symmetry plane of an Apollo-shaped capsule model and showed that the zone of modal amplification was much shorter in comparison to the length scales computed by Choudhari et al 25,26 for a roughness element with similar Re kk values in a flat plate flow. The authors speculated that the deviations to the ZPG result origin in the strongly favorable pressure gradient (FPG) on the capsule forebody.…”
Section: Introductionmentioning
confidence: 97%
“…An extensive summary of experimental work, which focuses on roughnessrelated transition in hypersonic boundary layers on blunt bodies, is given by Reda 8 and Schneider. 15 The mechanisms leading to transition behind a three-dimensional roughness are only partly understood, but work on mainly super-and hypersonic roughness-induced transition (carefully conducted experiments, 16,17 extensive DNS simulations [18][19][20][21][22] and results from global, 23 two-dimensional linear eigenvalue (LST-2D) [24][25][26][27] and three-dimensional parabolized (PSE-3D) 18,28 instability analyses) have considerably increased the knowledge in the recent years. However, most investigations have been performed on flat plates with a zero pressure gradient (ZPG) and a detailed study on the influence of different pressure gradients on roughness wake-flow instabilities is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…Despite several decades of experimental and numerical studies [6][7][8][9], the mechanism of the transition induced by the roughness element is only partly understood. Generally when a roughness element distorts the laminar boundary layer flow, two different types of instabilities are observed [10]: the convective instability and the absolute instability. The occurrence of the roughness element generates streamwise vortices behind it, then the lift-up mechanism of these vortices lead to the formation of a detached shear layer which is convectively instable in nature [11].…”
Section: Introductionmentioning
confidence: 99%